Humoral response to SARS‐CoV‐2 is well preserved and symptom dependent in kidney transplant recipients. Issue 12 (19th July 2021) - Magicova, Maria; Fialova, Martina; Zahradka, Ivan; Rajnochova‐Bloudickova, Silvie; Hackajlo, David; Raska, Petr; Striz, Ilja; Viklicky, Ondrej
Abstract : Data on the immune response to SARS‐CoV‐2 in kidney transplant recipients are scarce. Thus, we conducted a single‐center observational study to assess the anti‐SARS‐CoV‐2 IgG seroprevalence in outpatient kidney transplant recipients (KTR; n = 1037) and healthcare workers (HCW; n = 512) during the second wave of the COVID‐19 pandemic in fall 2020 and evaluated the clinical variables affecting antibody levels. Antibodies against S1 and S2 subunit of SARS‐CoV‐2 were evaluated using immunochemiluminescent assay (cut off 9.5 AU/ml, sensitivity of 91.2% and specificity of 90.2%). Anti‐SARS‐CoV‐2 IgG seroprevalence was lower in KTR than in HCW (7% vs. 11.9%, p = .001). Kidney transplant recipients with SARS‐CoV‐2 infection were younger ( p = .001) and received CNI‐based immunosuppression more frequently ( p = .029) than seronegative KTR. Anti‐SARS‐CoV‐2 IgG positive symptomatic KTR had a higher BMI ( p = .04) than asymptomatic KTR. Interestingly, anti‐SARS‐CoV‐2 IgG levels were higher in KTR than in HCW (median 31 AU/ml, IQR 17–84 vs. median 15 AU/ml, IQR 11–39, p < .001). The presence of moderate to severe symptoms in KTR was found to be the only independent factor affecting IgG levels (Beta coefficient = 41.99, 95% CI 9.92–74.06, p = .011) in the multivariable model. In conclusion, KTR exhibit a well‐preserved symptom‐dependent humoral response to SARS‐CoV‐2 infection. Abstract : Unvaccinated kidney transplant recipients who survived SARS‐CoV‐2 infection mount similar levels of anti‐spike protein antibodies as health care workers and levels increased with disease severity.